Turkey’s July 15th Coup: What Happened and Why: M. Hakan Yavuz and Bayram Balci, eds. Salt Lake City: The University of Utah Press, 2018. 360 pages. (American Journal of Islam and Society, 2018)
This book is a collection of essays written by a variety of experts on Turkey and social movements and provides a critical analysis of the role of the Gülen Movement (GM)—or Hizmet (“service”), as it is referred to by its adherents—in the coup attempt which was undertaken by one or more factions of the Turkish armed forces in July 2016. Edited and contributed to by M. Hakan Yavuz and Bayram Balci, this work began at a conference in October of 2016, where these experts gathered to discuss the coup itself as well as its implications and ramifications. The chapters in the book all build off of each other to some degree, with earlier chapters covering the history of the GM and the ways in which it has acquired influence both in Turkey and abroad; the coup and structural factors both within Turkish society; and the GM alliance with the Justice and Development Party (AKP) led by Recep Tayyip Erdoğan, the current president of Turkey. Later chapters expand in scope, covering the foreign policy implications of the coup both for Turkey and the United States, where Fethullah Gülen, the eponymous leader of the movement, resides today. Several chapters engage the state of the scholarship on the GM itself, effectively unpacking the ways in which the organization has actively co-opted academia by offering paid trips to Turkey, publishing non-peer-reviewed material, and funding conferences which avoid critical analysis of the GM. In the introduction Balci and Yavuz discuss the history of the Turkish state, giving particular focus to the place of religion under Kemal Atatürk; the pair discusses how the Turkish concept of secularism hews much more closely to the Jacobin tradition than the Anglo-American understanding. This is quite important as the alliance between the AKP and the GM (following Turkish elections in 2002 wherein the AKP swept to power) rested on a shared desire to overthrow the Kemalist conception of secularism, which seeks to dominate religion and prevent its expression in the public sphere. The book’s first chapter, written by Yavuz, charts the GM’s development over time, enumerating three key stages in its history. The first was that of a loosely bound religious network, encouraged by their leader to do good works; the second marked the expansion of the GM both within and outside of Turkey as an education-providing and media powerhouse; the third saw the GM create a parallel state structure in Turkey, which was mobilized to further increase the movement’s power throughout the 2000s and this current decade, most famously during the coup itself, though a variety of other incidents are discussed here and throughout the book. The next chapter details the coup itself, giving background which is necessary to understand the rest of the work and underlining four key junctures which put Turkey on the path to the July 15th event. The chapter’s author, Mujeeb R. Khan, notes that the structure of Turkish institutions (particularly its version of secularism), the continued domination of the Turkish deep state following the introduction of multi-party elections several decades ago, the neo-liberal opening Turkey experienced in the 1980s, and the rise of the AKP in the early 2000s all played integral roles in the rise of the GM and, eventually, the coup. Yavuz collaborated with Rasim Koç to write the third chapter, which examines the relationship between the GM and Erdoğan’s AKP (beginning with the unspoken alliance between the two which started after AKP’s 2002 electoral victory and whose disintegration led to the coup) as well as foreign policy consequences it had for Turkey. Chapters 4 and 5, written by Michael A. Reynolds and Kiliç Kanat, examine the coup, including the factors and events which led to both its occurrence and its failure. Kanat’s examination of why the coup failed is particularly interesting; he compares and contrasts the failure with previous successful coups which occurred in Turkey during the mid- to late-twentieth century. The next chapter, written by Caroline Tee, returns specifically to the topic of the AKP-GM relationship, digging deeply into the events which caused what on the surface seemed like a natural alliance to fracture and, during 2016, turn upon itself. Sabine Dreher’s chapter follows Tee’s, and is one of the most theoretical in the book, as it places the GM in the contexts of neoliberal and globalist theory, and notes internal contradictions within the movement itself. She considers how the global goals of the organization—the eradication of ignorance through educational work, the alleviation of poverty through private enterprise run by movement members, and the hosting of intercultural and interfaith dialogue— stand at odds with the nationalist project of the GM in Turkey, where movement members attempted to seize control of the state they had been infiltrating for some time as opposed to working outside of it. Balci wrote the eighth chapter, which deals with the GM movement’s presence in former Soviet satellites, namely Georgia, Azerbaijan, Uzbekistan, Turkmenistan, Kazakhstan, Kyrgyzstan, and Tajikistan. Following the coup attempt in 2016, the Turkish government pressured all of these states to shut down any GM movement activities within their countries, which was difficult as the GM provided excellent education to the children of elites in these nations. He then charts the differing reactions of the states mentioned above. The ninth chapter, by David Tittensor, turns to the structure of the GM and how secrecy and hierarchy play crucial roles in it, a reality which is often denied by the majority of scholarship—though he and other contributors to the work might dispute the use of the term “scholarship”, or at least qualify it. He does end his chapter with a criticism of the theory that GM members were key leaders of the coup, a conclusion which is at odds with that of most other contributors to the volume. The tenth chapter, by Yavuz Çobanoĝlu, provides insight into the role of women in the GM, criticizing some of Gülen’s writings and detailing the experiences of female students living in GM dormitories in Turkey, an experience that many of the women surveyed found to be repressive. Kristina Dohrn’s contribution outlines the activities and role of the GM movement in Tanzania, which, similar to Balci’s chapter, deals with repercussions of the coup and examines potential paths forward for the GM outside of Turkey. The work’s final chapter, written by Joshua Hendrick, is about how the GM presented itself as a “good” Islam in the wake of the 9/11 attacks, during a period in which the West writ large was searching for a “modern” version of the religion which it could champion in opposition to extremism. He effectively critiques the idea that religion itself can be good or bad, and rightly puts the onus on the actors themselves. The book ends with a postscript which examines the four major theories about how the coup may have come to pass, and comes to the conclusion that GM members were central and sole actors in the coup, which was in all likelihood approved by Gülen himself. This work does an excellent job of unpacking the GM and its various religious and political facets, even for the relatively uninitiated reader, and pushes back strongly against what it identifies as the prevailing anti-Erdoĝan Western narratives about the coup, which try to shift blame away from the GM and onto the shoulders of other actors, including the AKP leader. Particularly interesting is the book’s criticism of GM-sponsored scholarship, which is cited as one of the primary ways in which the GM has ingratiated itself worldwide, as it frames the group as “good” Islam. The work refrains from being speculative but does examine possible futures for the GM, mostly outside of Turkey, as the country’s government has gone to extreme lengths to uproot the movement in its homeland—lengths that the authors do rightly criticize as going too far, if somewhat tepidly at times. The US-Turkey relationship as it relates to the GM issue, specifically hisresidence in the US, is also examined in some depth and leads a student of either Islam in the US or the country’s politics to wonder if the GM has successfully insinuated itself into any institutions here, as it has done in Turkey. The author of this review once believed that Erdoĝan may have permitted or even been behind the coup attempt as a vehicle to consolidate power, but the evidence and arguments presented by the authors of this work have swayed his point of view; the GM was almost certainly responsible for the coup attempt, and it seems likely that Gülen himself gave his blessing to the members of his movement who carried it out.Grant MarthinsenMA, Center for Contemporary Arab StudiesGeorgetown University